Exploration of Research Hotspots in Technology-Enabled Oral English Teaching in China (2010-2025): Based on CiteSpace - Xi Chen; Weijie Hu (Journal of English Language Teaching and Linguistics, 2025)
Against the backdrop of advancing educational digitization, the auxiliary role of digital technology in oral English teaching has become increasingly prominent. As a global topic within the field of Computer-Assisted Language Learning (CALL), technology-enabled oral instruction manifests diverse pathways across different national contexts. This study employs CiteSpace 6.3.R1 software to conduct a visualization analysis of relevant journal articles indexed in China National Knowledge Infrastructure (CNKI) from 2010 to 2025. The aim is to explore research hotspots and evolutionary trends in technology-enabled oral English teaching within China. Results indicate a generally growing research interest in this field, with hotspots concentrated on the application of technologies such as artificial intelligence in higher education. However, the research still faces challenges:  empirical studies remain overly concentrated on higher education in terms of breadth, while in depth they mostly focus on verifying short-term effects, lacking in-depth examination of long-term impacts and ethical dimensions. By mapping China's research landscape, this study aims to provide a differentiated case reference for global research in this field. Future research should deepen toward a systematic approach characterized by multi-contextual, long-term, and deeply integrated approaches to build a more mature smart education ecosystem.